Epidemiology and disease burden of tuberculosis in children: a global perspective - Seddon, James A (Dove Medical Press, 2014)
Our understanding of the tuberculosis (TB) epidemic in children is incomplete due to challenges in diagnosis and reporting. Children have also been largely excluded from research and advocacy. However, the tide appears to be turning and interest in pediatric TB is increasing. In this article, we explore the epidemiology of childhood TB by first reviewing the natural history of TB in children and the factors that impact on each of the stages from exposure to disease. We then discuss how these factors affect what we see at a country and regional level. Finally, we assess the burden of childhood TB globally.